Fixed Point Results on Generalized Weakly Quasi-Type Contractive Operators - Chiroma, Rhoda; Shagari, Mohammed Shehu; Tanto, Ezra Emmanuel (Darul Yasin Al Sys, 2025)
This study introduces and investigates generalized weakly quasi-type contractive operators within the context of b-metric-like spaces, aiming to establish rigorous conditions for the existence and uniqueness of fixed points. While weakly contractive mappings have been widely examined in standard metric spaces, their behavior in b-metric-like spaces remains underexplored. Addressing this gap, the paper extends existing theoretical frameworks and contributes novel results relevant to this generalized setting. The proposed assertions are substantiated through non-trivial comparative examples, and several corollaries are presented to illustrate how the main findings generalize and unify various established results in fixed point theory. These contributions enhance the understanding of contractive mappings in non-standard metric-like structures and open pathways for further applications.